A Subtitling Analysis Of Expressive Utterances On The Dolphin Tale Movie - Nurjanah, Siti; , Dra. Dwi Haryanti M.Hum; , Siti Fatimah SPd.M.Hum (2013)
The aims of this research are to describe the type and intention of expressive utterance and to identify the types of subtitling strategies found in the Dolphin Tale Movie. The research studies about the subtitling strategy analysis of expressive utterances in Dolphin Tale Movie. This research applies descriptive qualitative research. By applying this method, the researcher uses the subtitle of Dolphin Tale Movie as the data source, while the data of the research are expressive utterance. As the comparison, there are also taken from manuscript to English and Indonesian. The technique of analysis applied in this study is descriptive analysis. The results of the research show that there are 72 data of expressive utterances. From 72 data of expressive utterances, the research finds seventeen kinds of expressive utterances, they are angry, sadness, happiness, pleasure, proud, apologyzing, regret, thanking, dislike, praise, requesting, afraid, hoping, greeting, permission, disagreeing, and agreeing. And the intention is to identified the meaning and types of expressive utterances which analyzed at the previous chapter both of source language and target language. Second, The subtitling strategies which are applied in Dolphin Tale movie are condensation, imitation, decimilation, deletion, paraphrase and transfer. Based on the analysis, the researcher finds 6 data or 8,4 % are translated using condensation strategy, 9 data or 12,5 % using imitation, 5 data or 6,9 % using decimilation, 4 data or 5,5 % using deletion, 12 data or 16,7 % using paraphrase and 36 data or 50 % using transfer